(untitled) (Jurnal Lemhannas RI, 2025)
Purpose: This study aims to gain an understanding of the characteristics of national leadership orientated towards the archipelago and examine the extent to which inclusive, equitable, and sustainable leadership practices serve as a strategic mechanism for strengthening national unity and resilience. The analysis focuses on Indonesia’s pluralistic socio-political dynamics, using the Asta Gatra framework as a conceptual lens to assess the relationship between leadership values, social cohesion, and the sustainability of national resilience. Study Design/Methodology/Approach: This research uses a qualitative descriptive approach through a review of academic literature, policy documents, and theoretical frameworks of leadership and governance to synthesise an understanding of national resilience from a Nusantara perspective. Findings: As a result, archipelago-orientated national leadership enhances national resilience by fostering social cohesion through inclusive leadership, promoting political and economic stability based on the principle of justice, and ensuring long-term sustainability by prioritising the environment, cultural values, and intergenerational responsibility within the Asta Gatra framework. Originality/Value: To the authors’ knowledge, limited scholarly attention has been devoted to examining leadership models that explicitly link Nusantara-orientated values with national resilience. In approaching this study, the authors did not assume that existing frameworks had sufficiently articulated how inclusivity, justice, and sustainability operate as practical governance mechanisms within Indonesia’s socio-political landscape. Nevertheless, this study offers a structured contribution by clarifying how such leadership orientations function in practice to strengthen national resilience, thereby providing a foundation for future scholarship in this field.